Prefabricated body for carbon-carbon composite material or carbon-ceramic composite material and preparation method thereof

By adopting a three-dimensional annular carbon fiber prefabricated body and multi-step process processing, a sandwich structure of the silicon carbide ceramic layer and the pyrolytic carbon layer is formed, which solves the problem of insufficient bonding strength between the prefabricated body of the carbon ceramic brake parts, and significantly improves the strength and friction performance of the material.

CN119874393APending Publication Date: 2025-04-25SHANGHAI XUANXI NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510072558.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing carbon ceramic brake parts prefabricated bodies are prone to layered damage under high-speed heavy load conditions, resulting in insufficient interlayer bonding strength and safety risks.

Method used

Using a three-dimensional annular carbon fiber prefabricated body, a high-strength braided layer is formed by winding the first and second orientation fibers that are oriented at a specific angle to the axial direction. Then, through CVI densification treatment and low-temperature graphitization treatment, the reaction melt implest is finally carried out to form a sandwich structure of the silicon carbide ceramic layer and the pyrolyzed carbon layer.

Benefits of technology

It significantly improves the bending strength and interlayer shear strength of carbon ceramic brake parts, improves the friction coefficient, reduces carbon fiber damage, and enhances the overall strength and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874393A_ABST
    Figure CN119874393A_ABST
Patent Text Reader

Abstract

The invention discloses a preform for a carbon-carbon composite material or a carbon-ceramic composite material, the preform is formed on the basis of a three-dimensional annular carbon fiber preform, and the preparation method adopts two times of CVI densification treatment, two times of graphitization treatment and two times of reaction melting infiltration so as to form a sandwich layer of a ceramic layer and a pyrolytic carbon layer. The friction plate of the carbon-ceramic composite material formed by the prefabricated body has a double-layer structure composed of a sandwich layer-shaped silicon carbide ceramic layer and a carbon layer, and the strength of the friction plate is higher than that of a carbon-ceramic brake disc prepared in the prior art. According to the preparation and weaving mode, the friction coefficient during braking is greatly improved, and the damage of formed silicon carbide to carbon fibers is finally avoided through two-time graphitization treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preform of a carbon-carbon composite material or a carbon-ceramic composite material and a preparation method thereof. Background Art

[0002] Carbon ceramic brake parts have shown broad application prospects in aerospace, high-speed trains, and high-end automobiles due to their light weight, high specific strength, excellent thermal stability, and wear resistance. There are two main methods for the preparation of traditional carbon ceramic brake parts: short fiber molded carbon ceramic brake parts and long fiber carbon ceramic brake parts. The short fiber molding process uses short-cut carbon fiber and resin raw materials to solidify the embryo by heating and molding, and then siliconizes to prepare carbon ceramic brake parts. The long fiber process uses a three-dimensional needle-punched carbon fiber preform, with a layer of mesh tire and a layer of non-weft cloth in a cyclic layering method, where the non-weft cloth is used alternately in the 0° and 90° directions, and the whole bundle of fibers is punctured and combined in the thickness direction, and then the carbon matrix is ​​densified by chemical vapor deposition and resin impregnation carbonization, and then the carbon ceramic brake parts are prepared by siliconization. The carbon ceramic brake preforms prepared by these two methods have the problem of low interlayer bonding strength, which is prone to safety risks of delamination damage under high-speed and heavy-load conditions. Therefore, finding a new weaving method to solve the problem of insufficient interlayer bonding strength can greatly improve the application scenarios of carbon ceramic brake parts.

[0003] With the development of technology, the preparation methods of carbon ceramic brake parts have gradually matured. The main siliconization processes include chemical vapor infiltration (CVI), precursor impregnation pyrolysis (PIP), etc. However, the use of the PIP process to prepare carbon ceramic brake parts will cause damage to the carbon fibers and reduce strength performance. The main form of carbon fiber damage is thermal stress physical damage, that is, the precursor attached to the surface of the carbon fiber is inorganicized at high temperature to form a ceramic body, accompanied by a large volume shrinkage. Under the traction of the carbon fiber, the volume shrinkage of the matrix appears in the form of cracking, and the orientation of the cracks is mainly perpendicular to the fiber axis. In the siliconization process, it was found that the first cycle of impregnation pyrolysis caused the greatest damage to the carbon fiber, and the strength loss rate of the carbon fiber was much greater than the sum of the strength losses of the carbon fiber in the subsequent multiple cycles of impregnation pyrolysis. The good uniformity of the matrix formed by the CVI siliconization process can reduce the residual thermal stress inside the material and has a low degree of damage to the carbon fiber.

[0004] With further research, people found that after the carbon matrix is ​​densified, using a higher graphitization temperature of more than 2000°C will cause microcracks in the carbon matrix wrapped around the carbon fiber, which will cause liquid silicon to flow into the carbon fiber surface during the siliconization process to form silicon carbide, causing carbon fiber damage, thereby affecting the performance of the finished carbon-ceramic brake composite material.

[0005] In the prior art, the processing and preparation of the preform is carried out in a selective manner until the subsequent high temperature treatment, and therefore it is difficult to avoid the disadvantages of this method. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem of low interlayer bonding strength caused by the existing weaving method and to provide an improved brake component preform and a preparation method thereof.

[0007] To this end, some embodiments of the present application provide a preform for a carbon-carbon composite material or a carbon-ceramic composite material, which is made of a three-dimensional annular carbon fiber preform, each layer of the three-dimensional annular carbon fiber preform includes a first oriented fiber that is wound and oriented to form a first angle with the axial direction of the three-dimensional annular carbon fiber preform, and a second oriented fiber that is wound and oriented to form a second angle with the axial direction of the three-dimensional annular carbon fiber preform; wherein the first angle or the second angle is greater than 0 degrees and less than 90 degrees, and at least one of the first fiber and the second fiber is carbon fiber.

[0008] In some embodiments, the first angles between the first oriented fibers wound in each layer of the three-dimensional annular carbon fiber preform and the axial direction are different; the second angles between the second oriented carbon fibers wound in each layer of the three-dimensional annular carbon fiber preform and the axial direction are different.

[0009] In some embodiments, both the first oriented fibers and the second oriented fibers are carbon fibers and are wound from the same carbon fiber bundle.

[0010] Other embodiments of the present application provide a method for preparing a carbon-carbon composite material, which includes: step 1: forming a three-dimensional annular carbon fiber preform of any one of the above items; step 2: the first CVI densification treatment: depositing the three-dimensional annular carbon fiber preform after high-temperature heat treatment in a deposition chamber using a carbon source gas; step 3: low-temperature graphitization treatment: low-temperature graphitizing the preform that has undergone the first densification to obtain the carbon-carbon composite material.

[0011] Some other embodiments of the present application provide a method for preparing a carbon-ceramic composite material, which includes: step 1: forming a three-dimensional annular carbon fiber preform of any one of the above items; step 2: the first CVI densification treatment: depositing the three-dimensional annular carbon fiber preform after high-temperature heat treatment in a deposition chamber using a carbon source gas; step 3: low-temperature graphitization treatment: low-temperature graphitizing the preform after the first densification; step 4: first reaction melt infiltration: embedding the preform after low-temperature graphitization in silicon powder, and placing it in a graphite crucible, placing it in a vacuum high-temperature furnace, and placing it in a high-temperature furnace for siliconization to obtain a carbon-ceramic brake blank, the carbon-ceramic brake blank has The first silicon carbide ceramic layer; step 5: a second CVI densification treatment, including placing the carbon-ceramic brake component blank back into the deposition chamber and depositing it using a carbon source gas; step 6: a high-temperature graphitization treatment, including high-temperature graphitizing the preform that has undergone the second densification treatment; step 7 a second reaction melt infiltration: embedding the preform that has undergone the high-temperature graphitization treatment in silicon powder, and placing it in a graphite crucible, placing it in a vacuum high-temperature furnace, and placing it in a high-temperature furnace for siliconization to obtain the brake component preform, the surface of the brake component preform has a second silicon carbide ceramic layer, thereby forming a sandwich ceramic layer of a silicon carbide ceramic layer and a pyrolytic carbon layer to obtain the carbon-ceramic composite material.

[0012] In some embodiments, the deposition temperature in step 2 is 850°C to 1150°C, the total deposition time is 300 to 400 hours, the first deposition time is 220 to 250 hours, the second deposition time is 30 to 50 hours, and the third deposition time is 30 to 100 hours. During the deposition process, each time the sample is taken out, it must be polished.

[0013] In some embodiments, the high temperature heat treatment in step 3 is performed at a temperature of 1500° C. to 1800° C. for a time of 2 to 8 hours.

[0014] In some embodiments, in step 4, the preform is embedded in silicon powder and placed in a graphite crucible, placed in a vacuum high-temperature furnace, raised to 1500-1650°C at a rate of 3-5°C / min, kept warm for 1-2 hours, and cooled to room temperature with the furnace, so that the first silicon carbide ceramic layer is obtained on the surface of the preform.

[0015] In some embodiments, the method for preparing a brake part preform according to claim 7 is characterized in that the deposition temperature in step 5 is 850°C to 1150°C, the total deposition time is 200 to 300 hours, the first deposition time in the deposition process is 100 to 150 hours, the second deposition time is 50 to 100 hours, and the third deposition time is 50 to 100 hours, and each time it is taken out during the deposition process, it must be polished.

[0016] In some embodiments, the high temperature heat treatment in step 6 is performed at a temperature above 2000° C. for a period of 2 to 8 hours.

[0017] In some embodiments, in step 7, the preform is embedded in silicon powder and placed in a graphite crucible, placed in a vacuum high-temperature furnace, raised to 1500-1650°C at a rate of 3-5°C / min, kept warm for 1-2 hours, and cooled to room temperature with the furnace, so that the second silicon carbide ceramic layer is obtained on the surface of the preform.

[0018] To this end, some embodiments of the present application provide a three-dimensional annular carbon fiber preform formed by winding and weaving carbon fibers, and graphitize the carbon matrix using two high-temperature graphitization methods. This method can better avoid insufficient interlayer bonding and carbon fiber damage, thereby achieving the purpose of improving strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of a process for preparing a carbon-ceramic composite material according to an embodiment of the present application.

[0020] Figure 2 It is a schematic structural diagram of a preform for a carbon-carbon composite material or a carbon-ceramic composite material according to an embodiment of the present application.

[0021] Figure 3 for Figure 2 An enlarged view of the structure of part A of the preform.

[0022] Figure 4 for Figure 2 An enlarged view of the structure of part B of the preform.

[0023] Figure 5 for Figure 3 Part C of the preform, i.e., an enlarged view of the structure of a single fiber at the end face. DETAILED DESCRIPTION

[0024] The specific embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0025] In one aspect, the present application provides a preform for a carbon-carbon composite material or a carbon-ceramic composite material, which is basically a three-dimensional annular carbon fiber preform 100, which can be composed of a woven layer containing only carbon fibers, and the weaving method of each woven layer is set so that each carbon fiber forms a preset angle with the working surface of the brake member, such as a brake disc of a car or a train. The working surface here is Figure 2 The end plane 10 in the XY direction is the braided layer. Figure 3 , Figure 4The material forming the three-dimensional annular carbon fiber preform may be carbon fiber only, or may be a mixture of carbon fiber and other fibers. To simplify the description, the three-dimensional annular preform obtained by the mixture is collectively referred to as a three-dimensional annular carbon fiber preform.

[0026] In one embodiment, the three-dimensional annular carbon fiber preform can be formed by a continuous braided layer through layered winding. For example, a first fiber is wound on a core column at unequal first angles and second angles, that is, a first oriented fiber F1 and a second oriented fiber F2 are formed. The first winding direction of the first oriented fiber F1 and the Z-axis direction have a first angle, such as Figure 4 As shown in α1, the angle between the second winding direction of the second oriented fiber F2 and the Z-axis direction is a second angle, that is, Figure 4 α2 shown in .

[0027] After completing the winding of one layer, the first angle and the second angle can be changed to achieve the winding of one layer radially outward, and so on until the expected radial size is obtained. Among them, the first oriented fibers F1 and the second oriented fibers F2 of each layer have different angles with the Z-axial direction, and the first oriented fibers F1 and the second oriented fibers F2 of each layer have different angles with the Z-axial direction from the first oriented fibers F1 and the second oriented fibers F2 of other layers. For example, 0° <

[0028] α1≠α2≠α3≠α4···≠α n <90°. Among them, α1 and α2 are the first angle and the second angle of the first layer, α3 and α4 are the first angle and the second angle of the second layer, and so on to α n-1 and α n are the first angle and the second angle of the n-1th layer.

[0029] It is also possible to use two mixed fibers, both of which are carbon fibers, or the first oriented fiber F1 can be carbon fibers, and the second oriented fiber F2 can be other types of fibers, such as natural fibers, composite fibers, etc. The carbon fibers can also be different types of carbon fibers to achieve different effects. For example, it can be polyacrylonitrile (PAN) based carbon fibers; asphalt based carbon fibers; viscose based carbon fibers; or small tow carbon fibers; large tow carbon fibers; high-strength carbon fibers, high modulus carbon fibers, etc. according to the tow specifications; and the mechanical properties can be high-strength carbon fibers, high modulus carbon fibers, etc., without limitation here.

[0030] like Figure 1 As shown, the step of preparing the three-dimensional annular carbon fiber preform can be used as the first step of preparing the brake preform, i.e., step 1. After the three-dimensional annular carbon fiber preform is formed, the subsequent process steps can be performed to obtain the brake preform.

[0031] Subsequent process steps include, for example:

[0032] Step 2: The first CVI process densification step. This step includes depositing the three-dimensional annular carbon fiber preform after high temperature heat treatment in a deposition chamber using a carbon source gas;

[0033] Step 3: First low-temperature graphitization treatment. This step includes subjecting the preform that has undergone the first CVI to low-temperature graphitization to obtain a low-temperature graphitized preform;

[0034] Step 4: first reaction melt infiltration, including embedding the low-temperature graphitized preform obtained in step 3 in silicon powder, placing it in a graphite crucible, placing it in a vacuum high-temperature furnace, and placing it in a high-temperature furnace for siliconization to obtain a carbon ceramic brake component blank having a first silicon carbide (SiC) ceramic layer;

[0035] Step 5: a second CVI densification treatment, including placing the carbon-ceramic brake component blank back into the deposition chamber and performing deposition using a carbon source gas;

[0036] Step 6: a second high-temperature graphitization treatment, comprising subjecting the obtained preform subjected to the second CVI densification treatment to high-temperature graphitization to obtain a high-temperature graphitized preform;

[0037] Step 7: The second reaction melt infiltration includes embedding the high-temperature graphitized preform in silicon powder, placing it in a graphite crucible, placing it in a vacuum high-temperature furnace, and placing it in the high-temperature furnace for siliconization to form a second SiC layer on the surface of the preform, thereby obtaining a sandwich-layered ceramic layer of SiC and C phases.

[0038] In the step 1, the brake component preform is woven in a spiral winding manner in which the carbon fibers are woven at a preset angle to the direction of the working surface of the brake disc, and the carbon fiber content is 100%.

[0039] In step 3, the deposition temperature is 850°C to 1150°C, and the total deposition time is 300 to 400 hours. The deposition process can be carried out in three times, the first deposition time is 220 to 250 hours, the second deposition time is 30 to 50 hours, and the third deposition time is 30 to 100 hours. During the deposition process, each time the sample is taken out, it must be polished.

[0040] The heat treatment temperature of the low-temperature graphitization in step 3 is 1500° C. to 1800° C., and the time is 2 to 8 hours.

[0041] In step 4, the preform that has undergone low-temperature graphitization is embedded in silicon powder, placed in a graphite crucible, placed in a vacuum high-temperature furnace, raised to 1500-1650°C at a rate of 3-5°C / min, kept warm for 1-2 hours, and cooled to room temperature with the furnace, so that the first SiC ceramic layer is obtained on the surface of the preform.

[0042] In step 5, the deposition temperature is 850°C to 1150°C, the total deposition time is 200 to 300 hours, and the deposition process can be completed in three times, wherein the first deposition time is 100 to 150 hours, the second deposition time is 50 to 100 hours, and the third deposition time is 50 to 100 hours. During the deposition process, each time the sample is taken out, it must be polished.

[0043] In step 6, the heat treatment temperature of high temperature graphitization is above 2000° C. and the time is 2 to 8 hours.

[0044] In step 7, the preform is embedded in silicon powder and placed in a graphite crucible, placed in a vacuum high-temperature furnace, and the temperature is raised to 1500-1650°C at a rate of 3-5°C / min, kept warm for 1-2 hours, and cooled to room temperature with the furnace to obtain a second SiC ceramic layer on the surface of the preform, thereby obtaining a sandwich-shaped ceramic layer of the SiC ceramic layer and the pyrolytic carbon layer.

[0045] It should be understood that in the above-mentioned preparation process of the carbon-ceramic composite material, if the high-temperature graphitization treatment in step 6 is stopped, a carbon-carbon composite material can be formed. Based on this, a carbon-carbon composite material can be formed.

[0046] The functions and effects of the present application are further described below through several embodiments. Specifically, embodiment 1 is a brake preform made of a conventional 90-degree cross-layered two-dimensional carbon fiber and web composite preform using a conventional process, and embodiments 2 to 5 are respectively embodiments of improved brake preforms formed by a secondary graphitization process using a three-dimensional all-carbon fiber preform according to the present application.

[0047] Example 1

[0048] The long fiber process uses a three-dimensional needle-punched carbon fiber preform, with a layer of mesh tire and a layer of carbon fiber non-woven cloth in a cyclic laying method. The carbon fiber non-woven cloth material is T700, and the directions are 0° and 90° alternately used. The whole bundle of fibers is punctured and combined in the thickness direction. Densification treatment is carried out in CVI, the deposition temperature is 1050°C, and the deposition time is 350 hours. During the deposition process, polishing and cleaning are carried out after each furnace exit; low-temperature graphitization is carried out in a graphitization furnace, the graphitization temperature is 2100°C, and the graphitization time is 6 hours; reaction melt infiltration treatment is carried out, the preform is embedded in silicon powder, and placed in a graphite crucible, placed in a vacuum high-temperature furnace, heated to 1600°C at a rate of 10°C / min, kept warm for 2 hours, and cooled to room temperature with the furnace to obtain a SiC ceramic layer on the surface of the preform.

[0049] Example 2

[0050] With 100% carbon fiber content, the carbon fiber T700 winding method is cross-winding along the axis of the brake disc. It is specified that one of the winding directions of the carbon fiber and the axial angle is α1, as shown in the figure α1, and the other winding direction of the carbon fiber and the axial angle is α2, as shown in the figure α2, α1 = 2°, α2 = 4°, α3 = 6°, α4 = 8°, α5 = 10°, α6 = 12°, etc., to form a three-dimensional annular carbon fiber preform; the three-dimensional annular carbon fiber preform is subjected to the first densification treatment in CVI, the deposition temperature is 1050°C, the deposition time is 350 hours, and each time it is taken out of the furnace during the deposition process, it is polished and cleaned; low-temperature graphitization is carried out in a graphitization furnace, the graphitization temperature is 1800°C, and the graphitization time is 6 hours; the first reaction melt infiltration treatment is carried out to form the preform The preform is embedded in silicon powder and placed in a graphite crucible, placed in a vacuum high-temperature furnace, heated to 1600°C at a rate of 10°C / min, kept warm for 2 hours, and cooled to room temperature with the furnace, so that a SiC ceramic layer is obtained on the surface of the preform; a second CVI densification treatment is performed, the deposition temperature is 1050°C, the deposition time is 250 hours, and polishing and cleaning treatment is performed each time after the furnace is taken out of the deposition process; high-temperature graphitization is performed in a graphitization furnace, the graphitization temperature is 2100°C, and the graphitization time is 6 hours; a second reaction melt infiltration treatment is performed, the preform is embedded in silicon powder, and placed in a graphite crucible, placed in a vacuum high-temperature furnace, heated to 1600°C at a rate of 10°C / min, kept warm for 3 hours, and cooled to room temperature with the furnace, so that a sandwich-layered ceramic layer of SiC and C phases is obtained on the surface of the preform, and a carbon-ceramic composite material is obtained.

[0051] Example 3

[0052] The carbon fiber content is 100%, and the carbon fiber T700 winding method is cross-winding along the axis of the brake disc. It is specified that one of the winding directions of the carbon fiber and the axial angle is α1, as shown in the figure α1, and the other winding direction of the carbon fiber and the axial angle is α2, as shown in the figure α2, α1 = 80°, α2 = 78°, α3 = 76°, α4 = 74°, α5 = 72°, α6 = 70°... to form a three-dimensional annular carbon fiber preform, and the three-dimensional annular carbon fiber preform is subjected to the first densification treatment in CVI, with a deposition temperature of 1050°C and a deposition time of 350 hours. During the deposition process, it is polished and cleaned after each furnace exit; low-temperature graphitization is carried out in a graphitization furnace, with a graphitization temperature of 1800°C and a graphitization time of 6 hours; the first reaction melt infiltration treatment is carried out to The preform is embedded in silicon powder and placed in a graphite crucible, placed in a vacuum high-temperature furnace, heated to 1600°C at a rate of 10°C / min, kept warm for 2 hours, and cooled to room temperature with the furnace, so that a SiC ceramic layer is obtained on the surface of the preform; a second CVI densification treatment is performed, the deposition temperature is 1050°C, the deposition time is 250 hours, and polishing and cleaning treatment is performed each time after the furnace is taken out of the deposition process; high-temperature graphitization is performed in a graphitization furnace, the graphitization temperature is 2100°C, and the graphitization time is 6 hours; a second reaction melt infiltration treatment is performed, the preform is embedded in silicon powder, and placed in a graphite crucible, placed in a vacuum high-temperature furnace, heated to 1600°C at a rate of 10°C / min, kept warm for 3 hours, and cooled to room temperature with the furnace, so that a sandwich-layered ceramic layer of SiC and C phases is obtained on the surface of the preform, and a carbon-ceramic composite material is obtained.

[0053] Example 4

[0054] With 100% carbon fiber content, the carbon fiber T700 winding method is cross-winding along the axis of the brake disc. It is specified that one of the winding directions of the carbon fiber and the axial angle is α1, as shown in the figure α1, and the other winding direction of the carbon fiber and the axial angle is α2, as shown in the figure α2, α1 = 2°, α2 = 4°, α3 = 6°, α4 = 8°, α5 = 10°, α6 = 12°... Thus, a three-dimensional annular carbon fiber preform is obtained, and the three-dimensional annular carbon fiber preform is subjected to the first densification treatment in CVI, with a deposition temperature of 1050°C and a deposition time of 350 hours. During the deposition process, it is polished and cleaned after each furnace exit; low-temperature graphitization is carried out in a graphitization furnace, with a graphitization temperature of 1700°C and a graphitization time of 6 hours; the first reaction melt infiltration treatment is carried out to The preform is embedded in silicon powder and placed in a graphite crucible, placed in a vacuum high-temperature furnace, heated to 1600°C at a rate of 10°C / min, kept warm for 2 hours, and cooled to room temperature with the furnace, so that a SiC ceramic layer is obtained on the surface of the preform; a second CVI densification treatment is performed, the deposition temperature is 1050°C, the deposition time is 250 hours, and polishing and cleaning treatment is performed each time after the furnace is taken out of the deposition process; high-temperature graphitization is performed in a graphitization furnace, the graphitization temperature is 2100°C, and the graphitization time is 6 hours; a second reaction melt infiltration treatment is performed, the preform is embedded in silicon powder, and placed in a graphite crucible, placed in a vacuum high-temperature furnace, heated to 1600°C at a rate of 10°C / min, kept warm for 3 hours, and cooled to room temperature with the furnace, so that a sandwich-layered ceramic layer of SiC and C phases is obtained on the surface of the preform, and a carbon-ceramic composite material is obtained.

[0055] Example 5

[0056] The carbon fiber content is 100%, and the carbon fiber T700 winding method is cross-winding along the axis of the brake disc. It is specified that one of the winding directions of the carbon fiber and the axial angle is α1, as shown in the figure α1, and the other winding direction of the carbon fiber and the axial angle is α2, as shown in the figure α2, α1=2°, α2=4°, α3=6°, α4=8°, α5=10°, α6=12°···to form the three-dimensional annular carbon fiber preform, and perform the first densification treatment on the three-dimensional annular carbon fiber preform in CVI, with a deposition temperature of 1050°C and a deposition time of 350 hours. During the deposition process, polishing and cleaning treatment is performed after each furnace exit; low-temperature graphitization is performed in a graphitization furnace, with a graphitization temperature of 1700°C and a graphitization time of 6 hours; the first reaction melt infiltration treatment is performed to form the preform The preform is embedded in silicon powder and placed in a graphite crucible, placed in a vacuum high-temperature furnace, heated to 1600°C at a rate of 10°C / min, kept warm for 2 hours, and cooled to room temperature with the furnace, so that a SiC ceramic layer is obtained on the surface of the preform; a second CVI densification treatment is performed, the deposition temperature is 1050°C, the deposition time is 250 hours, and polishing and cleaning treatment is performed each time after the furnace is taken out of the deposition process; high-temperature graphitization is performed in a graphitization furnace, the graphitization temperature is 2200°C, and the graphitization time is 6 hours; a second reaction melt infiltration treatment is performed, the preform is embedded in silicon powder, and placed in a graphite crucible, placed in a vacuum high-temperature furnace, heated to 1600°C at a rate of 10°C / min, kept warm for 3 hours, and cooled to room temperature with the furnace, so that a sandwich-layered ceramic layer of SiC and C phases is obtained on the surface of the preform, and a carbon-ceramic composite material is obtained.

[0057] The detailed performance parameters of the brake preform made of the carbon-ceramic composite material obtained in the embodiment with the end plane 10 as the working surface are shown in Table 1 below:

[0058] Table 1:

[0059] Friction coefficient Bending strength(MPa) Interlaminar shear strength (MPa) Example 1 0.35 180 20 Example 2 0.38 212 25 Example 3 0.39 205 26 Example 4 0.38 221 23 Example 5 0.35 227 21

[0060] As can be seen from the above table, the three-dimensional structure of the brake preform prepared by the present invention has a double-layer structure composed of sandwich-layered silicon carbide and carbon, that is, a carbon-ceramic composite material, and the bending strength and shear strength are both increased by about 20% compared with the carbon-ceramic brake disc prepared by the prior art. This preparation method also increases the friction coefficient during braking by about 10%. The friction coefficient can reach 0.39, for example, 0.38 to 0.39, the bending strength can reach 227MPa, for example, between 205 and 227MPa, and the interlayer shear strength can reach 26MPa, for example, 21 to 26MPa.

[0061] With further research, people found that after the carbon matrix is ​​densified, using a higher graphitization temperature of more than 2000°C will cause microcracks in the carbon matrix wrapped around the carbon fiber. During the infiltration process, liquid silicon will flow into the carbon fiber surface to form silicon carbide, causing damage to the carbon fiber, which will eventually lead to a reduction in the overall strength of the brake disc.

[0062] In the present invention, the two graphitization treatments ultimately prevent the formed silicon carbide from damaging the carbon fibers. Figure 5 As shown, the first graphitization temperature is relatively low, 1500°C to 1800°C, which will reduce the microcracks 21 in the structure of the first pyrolytic carbon layer 2, reduce the penetration of silicon carbide 3 into the surface of a single carbon fiber through the microcracks, and avoid damage to the surface of the carbon fiber; the second graphitization temperature is relatively high, 2000°C or above, which will increase the microcracks 41 in the structure of the second pyrolytic carbon layer 4, further increase the formation of silicon carbide in the microcracks, and the silicon carbide formed in the middle of the microcracks promotes the connection between the first silicon carbide (SiC) layer 3 and the second silicon carbide (SiC) layer 5. It is somewhat similar to the structure of needle puncture, which will eventually cause the uniformity of the silicon carbide structure of the carbon-ceramic brake disc and thus achieve the problem of improving the strength.

[0063] The above examples are only preferred embodiments of the present invention. Of course, those skilled in the art may make changes and modifications to the present invention. If these modifications and variations fall within the scope of the claims of the present invention and their equivalents, they should be considered to be within the scope of protection of the present invention.

Claims

1. A preform for a carbon-carbon composite material or a carbon-ceramic composite material, characterized in that: It is made of a three-dimensional annular carbon fiber preform, each layer of which includes a first oriented fiber whose winding orientation forms a first angle with the axial direction of the three-dimensional annular carbon fiber preform, and a second oriented fiber whose winding orientation forms a second angle with the axial direction of the three-dimensional annular carbon fiber preform; wherein the first angle or the second angle is greater than 0 degrees and less than 90 degrees, and at least one of the first fiber and the second fiber is carbon fiber.

2. The preform for carbon-carbon composite material or carbon-ceramic composite material according to claim 1, characterized in that: The first angles between the first oriented fibers wound on each layer of the three-dimensional annular carbon fiber preform and the axial direction are all different; the second angles between the second oriented carbon fibers wound on each layer of the three-dimensional annular carbon fiber preform and the axial direction are all different.

3. The preform for carbon-carbon composite material or carbon-ceramic composite material according to claim 1, characterized in that: The first oriented fibers and the second oriented fibers are both carbon fibers and are formed by winding a same carbon fiber bundle.

4. A method for preparing a carbon-carbon composite material, characterized in that: include: Step 1: forming a three-dimensional annular carbon fiber preform according to any one of claims 1 to 3; Step 2: First CVI densification treatment: depositing the three-dimensional annular carbon fiber preform after high temperature heat treatment in a deposition chamber using a carbon source gas; Step 3: low-temperature graphitization treatment: low-temperature graphitization is performed on the preform that has undergone the first densification to obtain the carbon-carbon composite material.

5. A method for preparing a carbon-ceramic composite material, characterized in that: include: Step 1: forming a three-dimensional annular carbon fiber preform according to any one of claims 1 to 3; Step 2: First CVI densification treatment: depositing the three-dimensional annular carbon fiber preform after high temperature heat treatment in a deposition chamber using a carbon source gas; Step 3: low temperature graphitization treatment: subjecting the preform that has undergone the first densification to low temperature graphitization; Step 4: First reaction melt infiltration: embed the low-temperature graphitized preform in silicon powder, put it in a graphite crucible, put it in a vacuum high-temperature furnace, and put it in a high-temperature furnace for siliconization to obtain a carbon-ceramic brake blank, which has a first silicon carbide ceramic layer; Step 5: a second CVI densification treatment, including placing the carbon ceramic brake component blank back into the deposition chamber and performing deposition using a carbon source gas; Step 6: high temperature graphitization treatment, including high temperature graphitization of the preform that has undergone the second densification treatment; Step 7: Second reaction melt infiltration: embed the preform that has been subjected to high-temperature graphitization treatment in silicon powder, place it in a graphite crucible, place it in a vacuum high-temperature furnace, and put it into the high-temperature furnace for siliconization to obtain the brake preform. The surface of the brake preform has a second silicon carbide ceramic layer, thereby forming a sandwich ceramic layer of a silicon carbide ceramic layer and a pyrolytic carbon layer to obtain the carbon-ceramic composite material.

6. The preparation method according to claim 4 or 5, characterized in that: In the step 2, the deposition temperature is 850°C to 1150°C, the total deposition time is 300 to 400 hours, the first deposition time is 220 to 250 hours, the second deposition time is 30 to 50 hours, and the third deposition time is 30 to 100 hours. During the deposition process, each time the sample is taken out, it must be polished.

7. The preparation method according to claim 4 or 5, characterized in that: In step 3, the high temperature heat treatment temperature is between 1500° C. and 1800° C., and the time is between 2 and 8 hours.

8. The preparation method according to claim 5, characterized in that: In step 4, the preform is embedded in silicon powder and placed in a graphite crucible, placed in a vacuum high-temperature furnace, raised to 1500-1650° C. at a rate of 3-5° C. / min, kept warm for 1-2 hours, and cooled to room temperature with the furnace, so that the first silicon carbide ceramic layer is obtained on the surface of the preform; The deposition temperature in step 5 is 850° C. to 1150° C., the total deposition time is 200 to 300 hours, the first deposition time is 100 to 150 hours, the second deposition time is 50 to 100 hours, and the third deposition time is 50 to 100 hours. During the deposition process, each time the sample is taken out, it must be polished. The high temperature heat treatment temperature in step 6 is above 2000°C and the time is 2 to 8 hours; In step 7, the preform is embedded in silicon powder and placed in a graphite crucible, placed in a vacuum high-temperature furnace, raised to 1500-1650°C at a rate of 3-5°C / min, kept warm for 1-2 hours, and cooled to room temperature with the furnace, so that the second silicon carbide ceramic layer is obtained on the surface of the preform.

9. The carbon-ceramic composite material formed according to the above method is characterized in that: The friction coefficient is 0.38-0.39, the bending strength is between 205-227MPa, and the interlaminar shear strength is 21-26MPa.

Citation Information

Cited By

  • Carbon-ceramic brake disc with composite functional layer and preparation method of carbon-ceramic brake disc

    CN120192166A